2019
DOI: 10.1111/andr.12585
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between cannabis and male infertility, sexual health, and neoplasm: a systematic review

Abstract: Background: In the United States of America (USA), cannabis is legal in 28 states for medical purposes and 8 states for recreational use. In 2016, the legal marijuana industry reached nearly $7 billion in sales in the USA alone. Although consumption continues to increase, the medical effects of marijuana remain understudied. Young males comprise the demographic most likely to consume cannabis, and these individuals will be most vulnerable to its short-and long-term consequences. Objective: The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 54 publications
0
36
0
2
Order By: Relevance
“…Other studies failed to demonstrate a decrease in sperm count in marijuana smokers [87]. A recent systematic review of seven clinical studies and 23 animal/in vitro studies concluded that cannabis consumption exerts a negative impact on semen parameters, but it considered also the alteration of sperm motility and morphology that is not an argument of our review [80].…”
Section: Effects On Spermatogenesismentioning
confidence: 79%
See 2 more Smart Citations
“…Other studies failed to demonstrate a decrease in sperm count in marijuana smokers [87]. A recent systematic review of seven clinical studies and 23 animal/in vitro studies concluded that cannabis consumption exerts a negative impact on semen parameters, but it considered also the alteration of sperm motility and morphology that is not an argument of our review [80].…”
Section: Effects On Spermatogenesismentioning
confidence: 79%
“…Despite animal studies showed a decreased testosterone production after exposition to cannabis, a clear relationship between marijuana use and hypogonadism has not been found in men. However, marijuana users have worse sperm parameters, including sperm total count and concentration, compared to controls in most studies [80].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this study, no differences in semen parameters were found comparing cannabis users with the rest of the sample. Recent systematic reviews support a negative effect of cannabis consumption on sperm parameters 109,110 and fertilizing capacity. 110 However, further studies are needed to validate these findings in relation to couple fertility.…”
Section: F I G U R Ementioning
confidence: 99%
“…Indeed, some studies have suggested a higher prevalence of erectile dysfunction (ED) among chronic cannabis users, whereas others have reported a prevalence that is equal to nonusers. 6 , 7 , 8 In a recent report, most male and female cannabis users endorsed increased sexual satisfaction, sensitivity, and orgasm intensity, with only a small fraction reporting orgasmic difficulty and some even reporting increased ability to orgasm. 9 Simultaneously, a large survey of Australian men found that daily cannabis use was associated with an inability to orgasm as desired, with either rapid ejaculation or delayed ejaculation.…”
Section: Introductionmentioning
confidence: 99%